A compact wideband monopole antenna fed by coplanar waveguide. (January 2016) - Pan, Guoping; Zhao, Wenhua; Zhou, Jiang; Su, Yan; Li, Qifu
Abstract: A compact wideband printed antenna fed by coplanar waveguide (CPW) is presented in this paper. The wideband characteristic is achieved by coupling three monopole resonant modes of the proposed antenna. The proposed antenna is built and simulated to verify the design strategy. A wide impedance bandwidth of 100.5% (1.7866-5.3953 GHz) with S11< - 10 dB is achieved. The proposed antenna has stable performance, including bi-directional radiation pattern and gain. It also shows the merits of low cost and simple structure.